The influence of negative emotions on adolescents' pathological gaming: the role of self-control in the associations with aggression, academic stress, and pathological gaming - Kim, Jeong Ae; Choi, Jae In; Lee, Sung Je; Jeong, Eui Jun (Frontiers in Psychology, 2025)
IntroductionLong-term exposure to negative emotions (e. g., anxiety, depression, loneliness) in adolescents has been reported to inhibit psychological growth and contribute to academic stress, aggression, and problem behaviors, including pathological gaming. However, there is a lack of longitudinal studies that examine the pathways through which academic stress and aggression, induced by negative emotions, lead to pathological gaming. This study aims to explore whether negative emotions significantly influence academic stress, self-control, and aggression, and whether self-control can mediate these pathways.MethodThis study analyzed 3 years of longitudinal data from Korean adolescent gamers (N = 968) using structural equation modeling. It aimed to explain how self-control mediates the pathways between negative emotions, academic stress, aggression, and pathological gaming, and to investigate the associations among these factors.ResultsNegative emotions were found to have a significant positive association with academic stress and aggression, but did not significantly associate with self-control. Furthermore, self-control was found to fully mediate the relationship between academic stress and pathological gaming, and partially mediate the relationship between aggression and pathological gaming. Therefore, while negative emotions did not directly influence self-control, they may affect other variables that, in turn, influence self-control, ultimately leading to pathological gaming. This finding is a key result of our study.DiscussionPreventing long-term exposure to negative emotions in adolescents and managing factors that influence self-control could be useful strategies for preventing pathological gaming. The results of this study suggest that continuous care for adolescents' psychological wellbeing and providing support to strengthen self-control could be effective interventions to suppress problem behaviors and foster healthy development in adolescents.